1245. Infection Prevention and Control (IP&C) and Antibiotic Stewardship (AS) Practices in Pediatric Long-Term Care Facilities. (26th November 2018) - Johnson, Candace L; Hill-Ricciuti, Alexandra; Saiman, Lisa
Abstract: Background: In November 2017, the Centers for Medicare and Medicaid (CMS) implemented a requirement for long-term care facilities (LTCFs) to incorporate AS into their IP&C programs. The purpose of this study was to describe baseline IP&C and AS practices in pediatric LTCFs. Methods: We modified a survey from the CDC to assess IP&C in pediatric LTCFs. The internet-based survey was distributed to the 41 pLTCFs in the Pediatric Complex Care Association from May to June 2017. The 67-question survey included questions to assess IP&C domains and infrastructure such as written policies, hand and respiratory hygiene (HH), personal protective equipment (PPE) use, environmental cleaning, and AS practices. Responses to questions were summarized using frequencies and analyzed using χ 2 or Fisher's exact tests, as appropriate. The characteristics of sites with ≥90% compliance with the CMS rule, as assessed by 14 relevant survey questions, were compared with those of sites with <90% compliance. Results: Overall, 25 (61%) facilities nationwide completed the survey. All sites reported having written IP&C policies and most had a person responsible for IP&C (96%); fewer reported reviewing/updating these policies annually (72%). Few sites provided feedback to staff on HH adherence (44%), PPE use (40%), and cleaning/disinfection procedures (44%). Few had written policies on antibiotic prescribing (48%) or provided prescribers with feedback about their prescribing practices (40%). Sites with ≥90% compliance with the CMS rule were more likely to report providing prescribers with feedback (70% vs. 20%, P = 0.03), to have provided AS training to clinical (60% vs. 0%, P < 0.01) and nursing staff (70% vs. 7%, P < 0.01) in the past 12 months, and to provide feedback regarding HH (70% vs. 27%, P = 0.05). Conclusion: While most facilities had implemented some IP&C and AS strategies pertaining to the CMS rule before its enforcement, this survey identified several gaps, especially pertaining to staff feedback for IP&C practices and antibiotic prescribing. Facilities should develop feedback strategies and regularly reinforce the importance of IP&C at employment and during regular trainings. Disclosures: All authors: No reported disclosures.